A case report of the rare fifteen-and-a-half syndrome. Issue 12 (March 2019) - Li, Mengmeng; Li, Xuan; Liu, Lina; Zhu, Mingsu; Lu, Dandan; Wang, Pei
Abstract: Rationale: The dorsal tegmentum of the caudal pons, including the medial longitudinal fasciculus (MLF), the paramedian pontine reticular formation (PPRF), abducens nucleus, and the adjacent facial nerve is the anatomical basis of the the fifteen and a half syndrome (15½) syndrome. No patients of 15½ Syndrome presenting with bilateral peripheral facial paralysis and one-and-a-half simultaneously at the onset have been reported up to now. Patient concerns: A 54-year-old woman complained of diplopia, slurred speech, and slightly distal numbness of the left upper limb for 4 days in our hospital. Diagnoses: The diffusion weighted image (DWI) and apparent dispersion coefficient (ADC) of MRI revealed the causative lesion in pons including bilateral pontine tegmentum and a narrow lesion along the midline in the right of the pons. Her clinical manifestations with results of MRI resulted in the diagnosis of the fifteen-and-a-half-syndrome. Interventions: The patient received antiplatelet aggregation, plaque stabilization, free radicals elimination, circulation improvement, nerves nourishment, and other symptomatic treatments. Outcomes: Two months later, her ocular movement recovered, and the bilateral facial paresis showed some improvement. Lessons: First, our patient with 15½ syndrome maybe one of mutants whose bilateral pontine tegmentum is supplied by unilateral pontine paramedian perforator artery. Second, DWI combined with ADC may be applied in the diagnosis of fifteen-and-half syndrome when the lesions of infarction are too small to be revealed by MRI scan.